2022
DOI: 10.1002/cssc.202200718
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Depolymerization of Lignin in a Biomass‐based Solvent**

Abstract: Breaking down lignin into smaller units is the key to generate high value‐added products. Nevertheless, dissolving this complex plant polyphenol in an environment‐friendly way is often a challenge. Levulinic acid, which is formed during the hydrothermal processing of lignocellulosic biomass, has been shown to efficiently dissolve lignin. Herein, levulinic acid was evaluated as a medium for the reductive electrochemical depolymerization of the lignin macromolecule. Copper was chosen as the electrocatalyst due t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 67 publications
0
24
0
Order By: Relevance
“…Park et al and Pintauro et al reported on the electrochemical oxidation and reduction of glucose to gluconic acid and sorbitol. , Governo et al elaborated on the electrochemical oxidation of xylose to xylonic acid in an alkaline medium . Electrochemical degradation of lignin to high value-added products has been exploited since the 20th century and remains popular, because of its high yield of aromatic compounds and carbohydrates, which can serve as feedstock for various platform chemicals. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…Park et al and Pintauro et al reported on the electrochemical oxidation and reduction of glucose to gluconic acid and sorbitol. , Governo et al elaborated on the electrochemical oxidation of xylose to xylonic acid in an alkaline medium . Electrochemical degradation of lignin to high value-added products has been exploited since the 20th century and remains popular, because of its high yield of aromatic compounds and carbohydrates, which can serve as feedstock for various platform chemicals. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…Organosolv-lignin, obtained from a formic acid-acetone extraction, also presents such an intense band at the same wavenumber . The high content of CO in unconjugated ketone, carbonyl, and ester groups, can be an advantage in some applications, such as electrochemical uses, due to the enhancement of protonic and electrical conductivity and electrokinetic stability . Therefore, lignins enriched with CO functional groups, like the ones obtained in this work, might be suitable precursors for electrode materials.…”
Section: Resultsmentioning
confidence: 64%
“…It is key to identify routes to increase dispersion of the polymer matrix, which may include the use of organic solvents and temperature, or a combination of both. Copper electrodes have been reported to degrade lignin biopolymer [22] . It is anticipated that improving the polymer‘s dispersion will increase the polymer‘s conversion efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Copper electrodes have been reported to degrade lignin biopolymer. [22] It is anticipated that improving the polymer's dispersion will increase the polymer's conversion efficiency.…”
Section: Proposed Mechanisms For Functionalization and Depolymerizationmentioning
confidence: 99%